Description The Activities of Recording and Reporting Maternal Health Monitoring in PWS-KIA Based on Surveillance Attributes - Ika Arma Rani; Arief Hargono (Jurnal Berkala Epidemiologi, 2014)
Maternal Mortality Ratio (MMR/AKI) in East Java Province tends to increase every year. Jember District had the highest number of maternal deaths during the 2009-2011 period and the second-highest in East Java in 2012. Public health center (PHC) of Kaliwates for 3 years in a row had the highest number of maternal deaths in Jember District. This study aims to describe the recording and reporting of maternal health monitoring activities in the Local Area Monitoring System on Maternal and Child Health (PWS-KIA) at the PHC of Kaliwates, Jember District, in 2012 using the surveillance attribute. The research design used is descriptive. The results showed that the current system was classified as complicated, lacked flexibility, low data quality, high acceptability, low sensitivity, low Positive Predictive Value (PPV/NPP), low representativeness, uncertain timelines, and low data stability. Alternative solutions offered are making routine follow-up plans from analysis of monitoring results, improving the quality of routine checks on the completeness and accuracy of data filling, standardizing all forms in the PWS-KIA and increasing the simplicity of forms, completing the PWS KIA manual at the PHC, making instructions technical form filling, taking notes on the mothers' cohort register by month, developing other surveillance systems for more specific cases, forming a Maternal and Child Health (MCH/KIA) surveillance team, perfecting attendance formats and using computerization.